2004
DOI: 10.1097/01.asn.0000130567.76794.58
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Increases Pax-2 Expression in Fetal Kidney Cells Via the AT2 Receptor

Abstract: Abstract. Although both the renin angiotensin system (RAS) and the paired homeobox 2 gene (Pax-2) seem critically important in renal organogenesis, whether and how they might interact has not been addressed. The present study asked whether a link between the RAS and Pax-2 exists in fetal renal cells, speculating that such an interaction, if present, might influence renal development. Embryonic kidney explants and embryonic renal cells (mouse late embryonic mesenchymal epithelial cells [MK4] and mouse early em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 62 publications
0
58
0
1
Order By: Relevance
“…32,85 Moreover, it has been shown that angiotensin II can stimulate the expression of Pax-2 through angiotensin II type 2 receptor and, therefore, affect nephrogenesis and kidney development. 86 …”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…32,85 Moreover, it has been shown that angiotensin II can stimulate the expression of Pax-2 through angiotensin II type 2 receptor and, therefore, affect nephrogenesis and kidney development. 86 …”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…36,53 The forward and reverse primers corresponding to mouse angiotensinogen, mouse renin, and ␤-actin cDNA 36,53 in RT-qPCR assays were as follows: Mouse angiotensinogen forward primer 5Ј-CCA CGC TCT CTG GAT TTA TC-3Ј and reverse primer 5Ј-ACA GAC ACC GAG ATG CTG TT-3Ј (NM_007428), mouse renin forward primer 5Ј-CTG GCC AAG TTT GAC GGT GTT-3Ј and reverse primer 5Ј-GTG TCC ACC ACT ACC GCA CAG-3Ј (BC061053), and ␤-actin forward primer 5Ј-CGT GCG TGA CAT CAA AGA GAA-3Ј) and reverse primer 5Ј-GCT CGT TGC CAA TAG TGA TGA-3Ј (NM_007393).…”
Section: Rt-qpcrmentioning
confidence: 99%
“…22,47,48 Briefly, small aliquots (20 to 50 l) of homogenized kidney explant sample were subjected to 10% SDS-PAGE and then transferred onto a polyvinylidene difluoride membrane (Hybond-P; GE Healthcare Biosciences, Baie d'Urfe, Quebec, Canada). The membrane was first blotted for anti-Pax-2 and then reblotted for ␤-actin.…”
Section: Western Blottingmentioning
confidence: 99%
“…For internal control, we deployed primers specific for mouse ␤-actin (forward and reverse primers 5Ј-CGT-GCGTGACATCAAAGAGAA-3Ј and 5Ј-GCTCGTTGCCAATAGT-GATGA-3Ј, corresponding to nucleotide sequences N ϩ 704 to N ϩ 724 and N ϩ 820 to N ϩ 840 of mouse ␤-actin cDNA [NM_007393]). 47 Immunohistochemistry Kidney explants were fixed in 4% paraformaldehyde in PBS (Fisher Scientific, Nepean, ON, Canada) after 24 h in culture and then paraffin embedded. Kidney sections of 5 m were deparaffinized in xylene and rehydrated.…”
Section: Rt-qpcrmentioning
confidence: 99%
See 1 more Smart Citation